The Impact of Opioid Receptor Gene Polymorphism on Fentanyl and Alfentanil’s Analgesic Effects in the Pediatric Perioperative Period - Lilic J; Marjanovic VG; Budic I; Stefanovic N; Stokanovic D; Marjanovic GT; Jevtovic-Stoimenov T; Golubovic M; Zecevic M; Velickovic-Radovanovic R (Dove Medical Press, 2024)
Jelena Lilic,1 Vesna G Marjanovic,1,2 Ivana Budic,1,2 Nikola Stefanovic,3 Dragana Stokanovic,4 Goran T Marjanovic,5,6 Tatjana Jevtovic-Stoimenov,7 Mladjan Golubovic,2,8 Maja Zecevic,9 Radmila Velickovic-Radovanovic4,10 1Clinic for Anesthesia and Intensive Therapy, University Clinical Centre Nis, Nis, Serbia; 2Department of Surgery and Anesthesiology with Reanimatology, Faculty of Medicine, University of Nis, Nis, Serbia; 3Department of Pharmacy, Faculty of Medicine, University of Nis, Nis, Serbia; 4Department of Pharmacology with Toxicology, Faculty of Medicine, University of Nis, Nis, Serbia; 5Department of Immunology, Faculty of Medicine, University of Nis, Nis, Serbia; 6Department of Hematology and Clinical Immunology, University Clinical Centre Nis, Nis, Serbia; 7Institute of Biochemistry, Faculty of Medicine, University of Nis, Nis, Serbia; 8Clinic of Cardiovascular and Transplant Surgery, University Clinical Centre Nis, Nis, Serbia; 9Clinic of Pediatric Surgery, University Clinical Centre Nis, Nis, Serbia; 10Clinic of Nephrology, University Clinical Centre Nis, Nis, SerbiaCorrespondence: Jelena Lilic, Clinic for Anesthesia and Intensive Therapy, University Clinical Centre Nis, Zorana Djindjica Blvd 48, Nis, 18000, Serbia, Tel +381605118400, Email jjeca8451@gmail.comIntroduction: The polymorphism of the gene coding mu-opioid receptor (OPRM1) is one of the factors contributing to the variability in the response to opioid analgesics in children. The goal of this study is to investigate its role in association with postoperative acute pain in children of various ages.Methods: This prospective study analyzed 110 pediatric patients, after plastic or orthopedic surgery, who were genotyped and randomly assigned to receive fentanyl or alfentanil. Postoperative pain was rated using Numerical Rating Scale (0- 10). All the patients were genotyped forOPRM1 118A>G (rs1799971) gene polymorphism.Results: School children under the age of 11 with the OPRM1 AA genotype were shown to have a higher BMI (p< 0.05). Children over the age of 12 carrying G allele OPRM1, had increased postoperative pain sensitivity and intensity (3.28± 1.95 vs 4.91± 2.17; p< 0.05), as compared to AA allele carriers.Discussion: OPRM1 118A>G polymorphism may explain the variation in the perception of postoperative pain in children over the age of 12 and may be a useful predictor for adjusting the dose of analgesics, but the dose is relative to the patient's needs regardless of his genetic characteristics. In younger children, carriers of polymorphic OPRM1 118G allele may be protected from obesity, due to diminished MOP expression.Keywords: polymorphism, OPRM1, opioid, pain, children